Węgrzy w Siedmiogrodzie w latach 1918–1938. Walka o ziemię, język i tożsamość - Kaczmarek, Karolina (Wydawnictwo "Rys", 2022)
The paper presents events that took place in Transylvania in the years 1918–1938, i.e. the process of shaping the borders, including the little-known episode of the Seklersian Uprising, and the fate of the Hungarian diaspora, which fell within the Romanian state after the Treaty of Trianon. Members of the Hungarian minority continued to experience problems related to maintaining their own culture, including the right to speak their own language. The paper describes the methods of pressure and legal solutions that were to lead to the domination of the Romanian language in the areas inhabited predominantly by the Hungarian population. These were, among others, restrictions in offices and workplaces, the principle of “numerus valachicus”, gradual limitation of education in Hungarian or causing the impoverishment of the Hungarian community, which resulted in mass emigration.
Hungarians in Transylvania in 1918–1938. Fight for Land, Language and Identity
Keywords: language rights; Transylvania; Seklers; national minorities; Trianon